A Composition-Based View of Organizational Ingenuity: Empirical Evidence from SMEs in India - Ibrahim, Nur Amalina Izyan Binti (Curtin University, 2022)
This thesis explores a relatively new concept of organizational ingenuity (OI) through the composition-based view (CBV) theory lens with SMEs in India. The unique conditions of emerging economy context of India are delineated to be factors that compel SMEs to develop ingenuity. Three conceptual properties of OI -strategy, capabilities, and process are validated as the components that support SMEs thrive despite challenging emerging economy conditions. Findings of this thesis are presented in a theoretical framework.